Analisa Kesiapan Dukungan Logistik Aviation Turbine Fuel (AVTUR) Jet A-1 Pada Masa Peningkatan Eskalasi Ancaman 2024 Sampai Dengan 2029 - Harahap, Eri Ahmad; Priyanto, Priyanto; Yadi, Rahman (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to see how the Analysis of the Readiness of Logistics Support Aviation Turbine Fuel (Avtur) Jet A-1 in the Period of Increased Threat Escalation 2024 Sd 2029 where the focus of the research is to explore the ability of Human Resources of Fuel Oil Management Personnel, especially the type of Avtur Jet A1 as the main fuel for TNI aircraft Air Defense Equipment, Management of Avtur Stock Readiness, Readiness of Avtur Storage facilities, Readiness of Avtur Service facilities and Distribution Facilities and Infrastructure capable of distributing to all TNI Military Bases. This research uses Mixed Method with data sources obtained through Questionnaires to 100 field personnel of TNI AU members, TNI members and Pertamina which are strengthened by interviews with BMP management officials at the Central level as policy makers, Operational and tactical levels in the field and literature studies. Data results are processed using Fish Bone analysis, Cause and Effect Matrix, SWOT Analysis, and SPSS 24 as a reliability test. This research shows that there is a need for improvement in the Readiness of Aviation Turbine Fuel (Avtur) Jet A-1 Logistics Support during the 2024 Sd 2029 Threat Escalation Period through a tiered education program at each Contingency-based rank level against the development of the Global, Regional and National strategic environment, utilization of large and extensive storage facilities with a high level of security to be able to accommodate Avtur in the Contingency framework, rejuvenation of modern service facilities and Avtur distribution infrastructure using Refuelling-capable Aircraft. With comprehensive development, it will increase the Readiness of Aviation Turbine Fuel (Avtur) Jet A-1 Logistics Support during the 2024 Sd 2029 Threat Escalation Period.Kata kunci: Kesiapan Dukungan Logistik, Avtur Jet A1, Peningkatan Eskalasi Ancaman